The relative performance levels of archers in ranking rounds and matches - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Major international target archery competitions include World Cups, World Championships and the Olympic Games. Those events include both a 72-arrow ranking round and then one-on-one ranked knock-out matches, until one archer or team remains. Previous modelling of the probabilities of winning podium positions at these events has assumed that the distance of an archer`s arrows from the centre of the target is normally distributed and that an archer`s performance levels in ranking rounds and matches are the same. This paper considers those two assumptions. For the top level of men`s recurve archers, this study determined that those assumptions are reasonable.